Depressive symptoms and levels of C-reactive protein: a population-based study - Pikhart, Hynek; Hubacek, Jaroslav A; Kubinova, Ruzena; Nicholson, Amanda; Peasey, Anne; Capkova, Nada; Poledne, Rudolf; Bobak, Martin (Social psychiatry and psychiatric epidemiology, 2009)
BACKGROUND: Depression and depressive symptoms have been repeatedly linked to elevated levels of C-reactive protein (CRP) but questions remain as to the statistical robustness of the association and particularly whether the association between depression and CRP reflects the presence of a chronic disease. METHODS: A random sample of 6,126 men and women aged 45-69 years was examined in a cross-sectional study in seven towns in the Czech Republic. Depressive symptoms were assessed by the Center for Epidemiologic Studies Depression (CESD) scale. RESULTS: Center for Epidemiologic Studies Depression score was significantly related to increased levels of CRP in a linear fashion. After controlling for a range of potential confounders, subjects with depressive symptoms (CESD score >or= 16) had CRP concentrations 0.43 mg/l (95% CI 0.16-0.72) higher than those without symptoms. The association remained significant when study sample was restricted to healthy subjects; among individuals who did not report any chronic disease, the difference between those with and without depressive symptoms was 0.44 mg/l (95% CI 0.14-0.74), and among persons who did not visit a doctor in the last 12 months the difference was 1.20 mg/l (95% CI 0.52-1.87). CONCLUSIONS: These results confirm that there is a statistically robust association between depressive symptoms and increased levels of CRP. We did not find evidence that the association is due presence of a chronic condition.
Keywords: průzkumy a dotazníky; Female; C-Reactive Protein; ženské pohlaví; průřezové studie; úzkostné poruchy; Surveys and Questionnaires; lidé; Anxiety Disorders; Cross-Sectional Studies; Male; Aged; Czech Republic; Česká republika; chronická nemoc; lidé středního věku; C-reaktivní protein; deprese; senioři; mužské pohlaví; Depression; Chronic Disease; Middle Aged; Humans